Etika Komunikasi Islam Dalam Sastra Lisan Aceh: Menelusuri Nilai-Nilai Religius Dan Sosial Budaya - Joko Hariadi; Abdullah; Nur Amelia (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Pendidikan, 2025)
Ethics is the main pillar in shaping a just and dignified social order. In Islam, ethics or morals come from the Qur'an and Sunnah which include communication principles such as qaulan sadida, qaulan ma'rufa, and qaulan layyina. Communication in Islam is not only informative, but also transformative, reflecting the value of faith, and forming collective consciousness. This study aims to reveal the representation of Islamic communication ethics in Acehnese oral literature as a medium of da'wah and character education. Using a qualitative approach and content analysis method, this research examines Acehnese literary texts. The results show that Acehnese oral literature conveys religious and moral messages through narratives that are contextual, rhetorical, and touch the spirituality of the listeners. Ethical values are conveyed subtly through local cultural symbols that are effective in internalizing da'wah messages. Oral literature is proven to be a grounded and relevant Islamic communication vehicle to shape the character and ethical awareness of society amid the challenges of the digital era.